Technical Analysis, Energy Cryptos and Energy Equity Markets - Gurrib, Ikhlaas (International Journal of Energy Economics and Policy, 2022)
The aim of this study is to investigate if Fibonacci retracements levels, as a popular technical analysis indicator, can serve to predict stock prices of leading US energy companies and energy crypto currencies. The methodology centers on the application of Fibonacci retracements as a trading system. Daily stock prices from the top ten constituents of the S&P Composite 1500 Energy Index are sourced, spanning from 21st November 2017 to 17th January 2020. The performance of the Fibonacci’s tool is captured using the Sharpe measure. The model is also benchmarked against the naÃ¯ve buy-and-hold strategy. We also tested if the use of Fibonacci retracements, coupled with a price crossover strategy results into higher return per unit of risk. Findings support the Fibonacci retracement tool captures the price movements of energy stocks better than energy cryptos. Further, price violations tend occur more during downtrends compared to uptrends, suggesting the Fibonacci tool does not capture price increases during downtrends as well as price decreases during uptrends. Less consecutive retracement breaks occurred as we move from 1 to 3 days prior. While a Fibonacci based strategy resulted in superior returns to a naÃ¯ve buy and hold model, the Sharpe and Sharpe per trade values were low. Complementing the Fibonacci tool with a price cross strategy did not improve the results significantly, and resulted in fewer or no trades for some constituents.